2019
DOI: 10.33155/j.ramd.2019.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of individualized physical rehabilitation programs for upper extremity disorders in women with post-mastectomy syndrome

Abstract: Objective: The aim of this study was to determine the effectiveness of individualized physical rehabilitation programs targeted at improving functional state of upper extremity in women with post-mastectomy syndrome. Method: Eighty five women with late symptoms of post-mastectomy syndrome were enrolled in the study. The participants were randomly enrolled for the first individualized program (Main Group, n=45) and for the second individualized program (Comparison Group, n=40). The first program included aqua a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…A great deal of research [2-4, 23, 24] indicates that women who underwent breast surgery and adjuvant therapy are more likely to present a higher risk of cardiotoxicity, reduced peak oxygen consumption, and impaired cardiopulmonary parameters. The importance of the problem is underlined by the presence of numerous physical exercise interventions [8][9][10][11][25][26][27][28] for improving life quality and functional state of the cardiovascular system in breast cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…A great deal of research [2-4, 23, 24] indicates that women who underwent breast surgery and adjuvant therapy are more likely to present a higher risk of cardiotoxicity, reduced peak oxygen consumption, and impaired cardiopulmonary parameters. The importance of the problem is underlined by the presence of numerous physical exercise interventions [8][9][10][11][25][26][27][28] for improving life quality and functional state of the cardiovascular system in breast cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed analysis of literary sources [4,9,10,13,23,24], including randomized clinical trials, pilot-analysis, and metaanalysis, showed that women after breast cancer treatment experienced radiotherapy-and chemotherapy-induced cardiovascular system adverse events, fatigue, and cardiotoxicity. Some papers considered aerobic physical activity [26] and water physical therapy [20,27,28] for pain and lymphedema reduction in post-mastectomy women, but they did not examine the effect of water exercises on the improvement of hemodynamic parameters in breast cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic benefits of yoga exercises have been used for reducing arm volume [9][10][11][12], anxiety, aggression and depression [13,14], and fatigue [15], as well as for improving range of motion [16], physical fitness [17], psychological health, and quality of life [18] in patients with breast cancer.…”
Section: Introductionmentioning
confidence: 99%